2(x+2) +8=6
2x +4 + 8=6
2x +12=6
2x= -6
x= -3
2006-11-15 05:05:52
·
answer #1
·
answered by Dutch Master 1
·
0⤊
2⤋
x=2
2006-11-15 05:05:39
·
answer #2
·
answered by psycho 3
·
0⤊
2⤋
2(x + 2) + 8 = 6
2x + 4 + 8 = 6
2x = 6 - 4 - 8
2x = -6
2x/2 = -6/2
x = -3
to check:
2(x + 2) + 8 = 6
2(-3 + 2) + 8 = 6
-6 + 4 + 8 = 6
6 = 6
- if the answer is equal (6 is equal to 6) then, the x is correct
2006-11-15 05:13:52
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
2(x + 2) + 8 = 6
2x + 4 + 8 = 6
2x + 12 = 6
2x = 6 -12
2x = -6
x = -6 / 2
x = -3.
because:
2(-3 + 2) + 8 = 6
2(-1) + 8 = 6
6 = 6.
2006-11-15 05:34:57
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
2(x+2)+8=6 remove brackets
2x+4+8=6 simplify(clean it up a bit)
2x+12=6 take 12 from both sides(if you take 12 from one side you must take it from the other side so it remains balanced)
2x=6-12 (just showing what im doing)
2x= -6 divide by two(you do this to get x on its own)
x= -3 answer!!!!
to proove that your right:
x= -3
2(x + 2) + 8 = 6 take the equation
2(-3 + 2) + 8 = 6 replace x with -3
-6+4+8=6 remove brackets
-2+8=6 simplify
6=6 answer.. this prooves x=-3 because the equation worked out....
2006-11-15 05:07:05
·
answer #5
·
answered by Join The Revolution! 2
·
2⤊
0⤋
2(x + 2) + 8 = 6 distribute 2
2x+4+8=6 combine like terms
2x+12=6 subtract 12 from each side
2x=-6 divide by 2
x=-3
2006-11-15 05:06:21
·
answer #6
·
answered by yupchagee 7
·
0⤊
0⤋
X= -3
2006-11-15 05:06:51
·
answer #7
·
answered by deadgrl6 2
·
0⤊
0⤋
2(x + 2) + 8 = 6
open bracket
2x + 4 + 8 = 6
move numbers to right
2x = 6 - 8 -4
2x = -6
div 2
x = -3
2006-11-15 05:06:10
·
answer #8
·
answered by rchlbsxy2 5
·
0⤊
1⤋
Everyone says distribute the 2 through the bracket - you don't gotta. Here is a different approach.
2 (x+2) +8 = 6
2 (x+2) = 6 - 8
2 (x+2) = (-2)
x + 2 = (-2) / 2
x + 2 = (-1)
x = (-1) - 2
x = (-3)
Same answer, different approach :)
2006-11-15 05:16:43
·
answer #9
·
answered by Mrs. Lucky 5
·
0⤊
0⤋
2(x+2) +8=6
2x +4 +8=6
-2x = -6
4+ 8 -6 = -2x
8+4(is 12) -6=6 sooo....
6= -2x (you have to get the x alone so divide by 2)
6= -2x
6/2 = -2x/2
-3=x or x=-3
2006-11-15 05:09:59
·
answer #10
·
answered by Life....it blows! 3
·
0⤊
1⤋
2(x + 2) + 8 = 6
2x + 4 + 8 = 6
2x + 12 = 6
2x + 12 - 12 = 6 - 12
2x = -6
2x/2 = -6/2
x = -3
2006-11-15 05:08:55
·
answer #11
·
answered by acehernandez2006 3
·
1⤊
0⤋